تحليل جغرافي سياسي للعلاقات التركية ومحيطها الإقليمي في منطقة الشرق الأوسط: الواقع والتحديات - الأحبابي، نصيف جاسم أسود سالم (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2021)
International relationship and give it the art of maneuvering in more than one region as it dominates a very large area as its importance comes from the confluence of the two continents of Asia and Europe, and separates it from the northern coasts of the African continent the Mediterranean, as this geographical location is granted Unique to Turkey is of great importance in addition to its regional and international standing It is characterized by geopolitical and strategic characteristics, which raises the question of the nature of Turkey's regional role towards the Middle East and the reasons for this trend, as well as the impact of the natural and human characteristics of Turkey and the Middle East on their direction, if we realize the fact that Turkey has been since the Justice and Development Party took power and its orientations towards the Islamic world and its role in changing the structure of Turkish relations With its regional neighborhood from 2002 to 2019 with reference to the contradictions resulting from regional and international changes that occurred in the region, as a result of the failure of its policy due to interference in the problems, which produced contradictions and complications during the rule of the Justice and Development Party. This was reflected in the future of the relationship in light of regional and international changes. Therefore, the importance of this study lies through the comprehensive geographical view on the influence of political geography on those international relations according to the spatial space that reflects the geographical and political dimension of Turkish relations and its regional surroundings in accordance with the principle of diplomatic cooperation economically and militarily, and the aspiration of Turkey to extend logistical influence in the Middle East region in a way A year and its neighboring countries in particular, in addition to the aggravation of the political crisis that the countries of the Middle East are going through in light of political and economic changes that led to the subjugation of several Arab cities to the control of terrorist groups, which made these countries in a weak point for the manufacture of For a political decision Consequently, Turkey has worked to develop a rapid strategy to limit the penetration of these groups towards the Turkish interior and limit its regional and international role, which has become clear how it is nourished from its external agendas working hard for political instability, according to a global strategy adopted by the United States of America towards the regions that possess a spatial and political sense And activating these terrorist groups to serve them in order to maximize nationalism over identity and sect over religion, in light of the destruction of those areas, which embody the reality and greatness of its population throughout history and in the various countries of the Middle East region from the perspective of political geography.
يعد موقع تركيا الجغرافي الاستراتيجي أحد أهم العوامل التي ساعدت على تطور علاقتها الدولية ومنحها فن المناورة في أكثر من منطقة واحدة كونها تهيمن على مساحة كبيرة جدا كما تأتي أهميتها من التقاء قارتين آسيا وأوروبا، ويفصلها عن السواحل الشمالية للقارة الأفريقية البحر المتوسط إذ يمنح هذا الموقع الجغرافي الفريد تركيا أهمية كبيرة بالإضافة إلى المكانة الإقليمية والدولية كونها تتميز بخصائص جيوسياسية واستراتيجية مما يثير مسألة طبيعة للدور الإقليمي لتركيا تجاه الشرق الأوسط وأسباب هذا الاتجاه وكذلك تأثير الخصائص الطبيعية والبشرية لتركيا والشرق الأوسط على اتجاههما، إن أدركنا حقيقة مفادها تركيا منذ تولي حزب العدالة والتنمية الحكم وتوجهاته نحو العالم الإسلامي ودوره في تغيير هيكل العلاقات التركية مع جوارها الإقليمي من ٢٠٠٢ إلى ٢٠١٩ مع الإشارة إلى التناقضات الناتجة عن التغيرات الإقليمية والدولية التي حدثت في المنطقة، كنتيجة لفشل سياستها بسبب التدخل في المشاكل مما أنتجت تناقضات وتعقيدات أثناء حكم حزب العدالة والتنمية. انعكس ذلك على مستقبل العلاقة في ضوء التغيرات الإقليمية والدولية. لذا تكمن أهمية هذه الدراسة من خلال النظرة الجغرافية الشاملة في تأثير الجغرافيا السياسية على تلك العلاقات الدولية وفق الحيز المكاني الذي يجسده البعد الجغرافي والسياسي للعلاقات التركية ومحيطها الإقليمي وفق مبدأ التعاون الدبلوماسي اقتصاديا وعسكريا، وما تطمح إليه تركيا من بسط نفوذ لوجستي في منطقة الشرق الأوسط بشكل عام ودول جواره الجغرافي بشكل خاص، إضافة إلى تفاقم الأزمة السياسية التي تمر بها دول الشرق الأوسط في ضوء متغيرات سياسية واقتصادية والتي أدت إلى إخضاع عدة مدن عربية لسيطرة الجماعات الإرهابية، مما جعلت تلك الدول في نقطة ضعف لصناعة القرار السياسي وبالتالي عملت تركيا على وضع استراتيجية سريعة للحد من تغلغل تلك الجماعات نحو الداخل التركي وتحجيم دورها الإقليمي والدولي، والذي بات واضحا كيف يتغذى من أجنده خارجية تعمل جاهدة إلى عدم الاستقرار السياسي له وذلك وفق استراتيجية عالمية تتبناها الولايات المتحدة الأمريكية اتجاه المناطق التي تمتلك حاسة مكانية وسياسية وتفعيل تلك المجاميع الإرهابية لخدمتها من أجل تعظيم القومية على الهوية والطائفة على الدين، في ضوء تدمير تلك المناطق والتي تجسد حقيقة وعظمة سكانها عبر التاريخ وفي مختلف دول إقليم الشرق الأوسط بمنظور الجغرافية السياسية.
Keywords: الجغرافيا السياسية -- صناعة القرار السياسي -- التعاون الدبلوماسي -- العلاقات الإقليمية -- الشرق الأوسط